2006
DOI: 10.1111/j.1600-0889.2006.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloud droplet activation of polymerized organic aerosol

Abstract: High‐molecular‐weight organic compounds represent an important fraction in atmospheric aerosols, but their interactions with atmospheric water vapour are not well understood. Specifically, the hygroscopicity of polymerized atmospheric aerosols is larger than expected for their high molecular weights and is not a strong function of the degree of polymerization, but their cloud‐nucleating activity declines as polymerization progresses. We apply a Flory–Huggins based theory for polymer–water interactions to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 38 publications
5
52
2
Order By: Relevance
“…In agreement with results of previous studies of the hygroscopicity of polymers and HULIS, we observed little variability in hygroscopic growth across PEG systems with different molecular masses (Brooks et al, 2004;Petters et al, 2006;Ziese et al, 2008). HGFs measured here are within ∼ 5 % of those measured for 100 nm (dry size) particles comprised of PEG with average molecular masses of 600 and 3400 measured by Petters et al (2006). In general, results were similar for the PEG-AS systems; however, at RHs of 80 and 90 %, greater growth was observed for PEG200-AS particles (HGFs = 1.39 and 1.60) compared to PEG1000-AS (HGFs = 1.24 and 1.38) and PEG10000-AS particles (HGFs = 1.35 and 1.42).…”
Section: Measurements Of Hygroscopic Growth and Ccn Activitysupporting
confidence: 81%
See 2 more Smart Citations
“…In agreement with results of previous studies of the hygroscopicity of polymers and HULIS, we observed little variability in hygroscopic growth across PEG systems with different molecular masses (Brooks et al, 2004;Petters et al, 2006;Ziese et al, 2008). HGFs measured here are within ∼ 5 % of those measured for 100 nm (dry size) particles comprised of PEG with average molecular masses of 600 and 3400 measured by Petters et al (2006). In general, results were similar for the PEG-AS systems; however, at RHs of 80 and 90 %, greater growth was observed for PEG200-AS particles (HGFs = 1.39 and 1.60) compared to PEG1000-AS (HGFs = 1.24 and 1.38) and PEG10000-AS particles (HGFs = 1.35 and 1.42).…”
Section: Measurements Of Hygroscopic Growth and Ccn Activitysupporting
confidence: 81%
“…These HGFs correspond to κ HGF,app values of 0.162 and 0.133. In agreement with results of previous studies of the hygroscopicity of polymers and HULIS, we observed little variability in hygroscopic growth across PEG systems with different molecular masses (Brooks et al, 2004;Petters et al, 2006;Ziese et al, 2008). HGFs measured here are within ∼ 5 % of those measured for 100 nm (dry size) particles comprised of PEG with average molecular masses of 600 and 3400 measured by Petters et al (2006).…”
Section: Measurements Of Hygroscopic Growth and Ccn Activitysupporting
confidence: 79%
See 1 more Smart Citation
“…Only small changes are expected for i s . Overall a decrease of κ is expected under the influence of oligomerization, though the effect becomes smaller with increasing M s (Petters et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that the FH approach is suitable to describe the absorption of water by polymerized organic aerosol particles (Petters et al, 2006) and by water-miscible organic solids that are in a rubbery state (Hancock and Zografi, 1993;Zografi, 2000, 2001). For FH modeling, we assumed φ s = g −3 m and f = (M s /ρ s )/(M w /ρ w ) based on volume additivity, and we inserted a w from Eq.…”
Section: A34 Flory-huggins Modelmentioning
confidence: 99%